Use Of Colour Doppler Ultrasonography In Early Assessment Of Dialysis Access Complications In Patients Undergoing Surgery For Hemodialysis Access. - Mushtaq Ch, Sumera; Murtaza, Ghulam; Fatima, Kiran; Butt, Batool; Kazmi, Kumail; Hussain, Tassawar (Journal of Rawalpindi Medical College, 2025)
Objectives: A majority of patients all over the world with renal failure in the late stage of the disease need regular hemodialysis for maintaining a good quality of life. Making an arterio-venous (AV) fistula is the most common way to have vascular access for doing hemodialysis in these patients. Our study aimed to see the use of colour Doppler ultrasound (CDU) in the early diagnosis of ischemic steal syndrome (ISS) in patients with AV fistula for hemodialysis. Methods: We conducted this study in the Nephrology and Radiology departments of Fauji Foundation Hospital, Rawalpindi. The study was a prospective, cross-sectional trial conducted on sixty patients of chronic renal failure who were on hemodialysis and advised to have an arterio-venous fistula in the upper extremity. Patients had having age range in age from 20 to 70 years. Colour Doppler ultrasound was done, and assessment of the line and its complications along with PSV (Peak Systolic Velocity) and EDV (End Diastolic Volume) measurement was done by an expert Radiologist.. The proximal, mid, and distal outflow veins were examined for patency, diameters, and mean velocities. The extent of the stenosis was calculated where there was stenosis. Results: The Majority of the patients had normal vessel calibre, with 13 patients (21.6%) having a BB fistula, 15 patients (25%) having an RC fistula, and 32 patients (53%) having a BC fistula. Our study had shown a mean age of AVF maturation of 3.07 ± 0.389 weeks after its 1st creation. Five patients (8.3%) had an uncomplicated outcome, and 55 patients (91.6%) had a shunt complication of 90%. A significant venous thrombosis was seen in 24 patients(40%), stenosis in 18 patients(30%), aneurysmal dilatation in 12 patients(20%), pseudo-aneurysmal formation in 6 patients(10%) and last but not least steal syndrome in 2 patients(3.3%,). Conclusion: Early recognition and management of an abnormal fistula in hemodialysis patients can improve the outcome in chronic renal failure patients and reduce the incidence of ischemic steal syndrome and other complications. Keywords: Colour Doppler Ultrasonography, Hemodialysis, AV fistula, Ischemic steal syndrome